Pengaruh Pelatihan, Kompensasi Dan Motivasi Terhadap Kinerja Karyawan Departemen Quality Pt Pci Elektronik Internasional Di Kota Batam - Nuraeni, Brigida Endah; Sitompul, Elpiani Togumarina; Harianja, Josepin (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2022)
This study aims to determine the effect of training, compensation and motivation on the performance of employees of the Quality Department of PT PCI Elektronik Internasional in Batam City. This research was conducted using quantitative methods. Sampling used the Slovin formula with 89 respondents. The data collection technique uses a questionnaire and is distributed via the Google form. Data analysis using SPSS. The results of the study found that the training variable had a tcount of 4.921 > ttable of 1.662 with a significance value of 0.000 <0.05, then H0 was rejected and Ha was accepted, the compensation variable had a tcount of -2.316 <ttable 1.662 and a significance value of 0.023 <0.05, then H0 accepted and Ha rejected the motivational variable has a tcount of 4.514 > ttable of 1.662 and a significance value of 0.000 <0.05, then H0 is rejected and Ha is accepted. The three variables namely training, compensation and motivation together have an Fcount of 74.156 > Ftable of 2.71 and a significance value of 0.000 <0.05. This shows that simultaneously training, compensation and motivation have a positive and significant effect on the performance of PT PCI Quality Department employees. The relationship between variables can be written by the equation Y=13.048+0.381X1-0.290X2+0.472X3. The effect of the independent variable on the dependent variable is 72.4% while the remaining 27.6% is influenced by other factors not examined.